Synthesis of benzotriazole-intercalated dispersions of molybdenum, tungsten and vanadium oxides for tribochemical applications - Logvinovich, Aliaksandr S.; Sviridova, Tatsiana V.; Agabekov, Vladimir E.; Sviridov, Dmitry V. (Journal of the Belarusian State University. Chemistry, 2021)
The effect of dispersed particles of lamellar molybdenum, tungsten and vanadium oxides on the lubrication properties of mineral oil was investigated. It is shown that in the presence of particles of hexagonal molybdenum oxide the coefficient of friction falls two-fold (from 0.08 to 0.04) exhibiting further decrease under high mechanical load, i. e. molybdenum oxide behaves as an adaptive lubricant. The intercalation of benzotriazole into molybdenum oxide ensures additional reduction of mechanical wearing due to suppressing the tribocorrosion.